Policy Interventions Targeting NEETs in Different Institutional Settings - Sue Maguire; Mark Levels; Christian Brzinsky-Fay; Janine Jongbloed; Hirofumi Taki (The Dynamics of Marginalized Youth, 2022)
This chapter discusses the types of policy initiatives which have been introduced to address concerns over the ongoing 'problem' of not in education, employment, or training (NEETs) young people. Early intervention policies have been introduced in many countries in an attempt to provide early identification of young people who may be at risk of becoming NEET or dropping out of education. Approaches for identifying those at risk of becoming NEET are therefore focused on whether young people will remain in education, employment, or training following the completion of compulsory education. Reintegration strategy at the level of the individual should involve having systems which identify young people who become NEET and support them to achieve positive outcomes in terms of re-engagement.
Keywords: 300